Profiling of mouse macrophage lipidome using direct infusion shotgun mass spectrometry - Hsieh, Wei-Yuan; Williams, Kevin J.; Su, Baolong; Bensinger, Steven J. (STAR protocols, 2021)
Immune cells, such as macrophages, reprogram their lipid metabolism in response to the activation of pattern recognition receptors (e.g., TLRs, NLRs) and cytokine receptors (e.g., interferons, interleukins). Profiling these changes can be achieved with shotgun mass spectrometry. This protocol provides step-by-step instructions on the generation and stimulation of bone marrow-derived macrophages (BMDMs), sample collection, and lipid extraction for profiling the macrophage lipidome. For complete details on the use and execution of this protocol, please refer to Hsieh et al. (2020). [Display omitted] •Protocol for profiling mouse macrophage lipidome with direct infusion mass spectrometry•Provides quantitative measurements of immune cell lipid composition•Includes cell culture, cell imaging, sample preparation, and data output analysis•Can be adapted for different lipidomics-mass spectrometry platforms Immune cells, such as macrophages, reprogram their lipid metabolism in response to the activation of pattern recognition receptors (e.g., TLRs, NLRs) and cytokine receptors (e.g., interferons, interleukins). Profiling these changes can be achieved with shotgun mass spectrometry. This protocol provides step-by-step instructions on the generation and stimulation of bone marrow-derived macrophages (BMDMs), sample collection, and lipid extraction for profiling the macrophage lipidome.